Mechanical underwater adhesive devices for soft substrates - Ziliang Kang; Johanna A. Gomez; Alisa MeiShan Ross; Ameya R. Kirtane; Ming Zhao; Yubin Cai; Fu Xing Chen; Corona L. Chen; Isaac Diaz Becdach; Rajib Dey; Andrei Russel Ismael; Injoo Moon; et al. (Nature, 2025)
Abstract Achieving long-term underwater adhesion to dynamic, regenerating soft substrates that undergo extreme fluctuations in pH and moisture remains a major unresolved challenge, with far-reaching implications for healthcare, manufacturing, robotics and marine applications1–16. Here, inspired by remoras—fish equipped with specialized adhesive discs—we developed the Mechanical Underwater Soft Adhesion System (MUSAS). Through detailed anatomical, behavioural, physical and biomimetic investigations of remora adhesion on soft substrates, we uncovered the key physical principles and evolutionary adaptations underlying their robust attachment. These insights guided the design of MUSAS, which shows extraordinary versatility, adhering securely to a wide range of soft substrates with varying roughness, stiffness and structural integrity. MUSAS achieves an adhesion-force-to-weight ratio of up to 1,391-fold and maintains performance under extreme pH and moisture conditions. We demonstrate its utility across highly translational models, including in vitro, ex vivo and in vivo settings, enabling applications such as ultraminiaturized aquatic kinetic temperature sensors, non-invasive gastroesophageal reflux monitoring, long-acting antiretroviral drug delivery and messenger RNA administration via the gastrointestinal tract.